Fast ion emission and parametric instabilities in laser-solid target interaction. (5th April 2016) - Curcio, A.; Andreoli, P.; Barbarino, M.; Bonasera, A.; Cipriani, M.; Consoli, F.; Cristofari, G.; Angelis, R. De; Giorgio, G. Di; Galletti, M.; Giulietti, D.; Ingenito, F.
Abstract: The spectrum of the accelerated ions at the laser ABC of ENEA research institute, detected by time of flight measurements, is correlated to the onset of parametric instabilities, evidenced by optical diagnostics. In fact, the emission of the laser harmonics, 2 ω and 3/2 ω, in the visible spectrum manifests the existence, inside the inhomogeneous plasma, of regions in which electron plasma waves can be generated. These waves are the tool for the production of a supra-thermal electron population, responsible for the creation of an electric potential at the plasma sheath, which drives the ion acceleration.